Including the Dark Side of Entrepreneurship in the Entrepreneurship Education - Pawel Ziemianski; Jakub Golik (MDPI AG, 2020)
Pursuing an entrepreneurial career is often rewarding in terms of both economic and psychological outcomes. However, becoming an entrepreneur also has its darker side that affects professional and personal life. Meanwhile, the positivity bias is prevalent in entrepreneurial education and research. It is recognized as emphasizing the advantages of becoming an entrepreneur and giving considerably less attention to potential downsides. Based on the theoretical model of met expectations, it is proposed that building an accurate and balanced image of the entrepreneurial career is crucial to help students prepare to pursue it successfully. Using data from SEAS (Survey on Entrepreneurial Attitudes of Students) Project, authors quantitatively test the perception of the severity of negative aspects of entrepreneurship among 513 business students from northern Poland. Further, the results of 16 semi-structured qualitative interviews conducted with mature and experienced entrepreneurs from the same region are presented. They are focused on the entrepreneurs' perspective on the experienced dark sides and reveal employed coping strategies. A call is made to include these findings in designing university entrepreneurship programs by eliciting the awareness of the existence of the dark sides and indicating the means of their attenuation.